The heat shock transcription factor PsHSF1 of Phytophthora sojae is required for oxidative stress tolerance and detoxifying the plant oxidative burst. (9th October 2014) - Sheng, Yuting; Wang, Yonglin; Meijer, Harold J. G.; Yang, Xinyu; Hua, Chenlei; Ye, Wenwu; Tao, Kai; Liu, Xiaoyun; Govers, Francine; Wang, Yuanchao
Summary In the interaction between plant and microbial pathogens, reactive oxygen species (ROS) rapidly accumulate upon pathogen recognition at the infection site and play a central role in plant defence. However, the mechanisms that plant pathogens use to counteract ROS are still poorly understood especially in oomycetes, filamentous organisms that evolved independently from fungi. ROS detoxification depends on transcription factors (TFs) that are highly conserved in fungi but much less conserved in oomycetes. In this study, we identified the TF PsHSF1 that acts as a modulator of the oxidative stress response in the soybean stem and root rot pathogen Phytophthora sojae. We found that PsHSF1 is critical for pathogenicity in P. sojae by detoxifying the plant oxidative burst. ROS produced in plant defence can be detoxified by extracellular peroxidases and laccases which might be regulated by PsHSF1. Our study extends the understanding of ROS detoxification mechanism mediated by a heat shock TF in oomycetes.